Transforming Licensing Regulations: Legal Implications for Administrative Governance in Indonesia - Didi Nursidi (Sultan Publisher, 2023)
This fundamental change in the legal architecture of licensing has complex and multi-layered implications for government administrative governance, particularly regarding the redistribution of authority between government institutions, a paradigm shift from obligation-based licensing to risk-based licensing, and the restructuring of the legal responsibilities of administrative officials in the digital licensing ecosystem. This study aims to analyze the legal implications of the transformation of licensing regulations on administrative governance in Indonesia, map the shift in institutional legal responsibilities post-reform, and formulate a framework for adapting administrative law that is responsive to the dynamics of the digital technology-based licensing system. The research employed a normative juridical method reinforced by an empirical juridical approach. Analysis of primary and secondary legal documents was combined with in-depth interviews with 52 informants, including administrative law academics, officials from the Ministry of Investment/BKPM, regional regulators, business actors, and judges at the State Administrative Court in three major cities . Data were analyzed using an integrated statute, conceptual, and case approach within a transformative legal implications analysis framework. The findings identify four main legal implications of the transformation of licensing regulations: (1) a shift in the legal paradigm from ex-ante to ex-post, which changes the nature of administrative officials' legal responsibilities; (2) a restructuring of the state administrative lawsuit mechanism against digital licensing decisions; and (3) a weak legal protection framework for business actors who rely on self-declaration-based standard certificate conformity. This research produces a transformative licensing administrative legal adaptation framework that serves as an academic and policy reference for administrative law reform in the era of digital licensing governance.